2008
DOI: 10.1139/z08-050
|View full text |Cite
|
Sign up to set email alerts
|

Visual specialization of an herbivore prey species, the white-tailed deer

Abstract: To gain knowledge of visual specializations influencing the behavior of white-tailed deer ( Odocoileus virginianus (Zimmermann, 1780)), we examined gross eye characteristics, structural organization of the retina, and the density and distribution of cone photoreceptors. White-tailed deer possess ocular features similar to other ungulates including a horizontal slit pupil, reflective tapetum lucidum, typical retinal structure, and medium wavelength sensitive cone photoreceptors concentrated in a horizontal visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…Rabin et al, 2006). In addition, prey animals like reindeer react to movements in their sight and might move away from moving objects as a strategy to avoid the risk of predation (D'Angelo et al, 2008;Heesy, 2004). Open areas are generally considered the preferred locations chosen by prey animals to allow them to scan for predators (e.g., Altendorf, Laundré, Gonzalez, & Brown, 2001), which was also realized in the preference of heaths and clear cuts within the home ranges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rabin et al, 2006). In addition, prey animals like reindeer react to movements in their sight and might move away from moving objects as a strategy to avoid the risk of predation (D'Angelo et al, 2008;Heesy, 2004). Open areas are generally considered the preferred locations chosen by prey animals to allow them to scan for predators (e.g., Altendorf, Laundré, Gonzalez, & Brown, 2001), which was also realized in the preference of heaths and clear cuts within the home ranges.…”
Section: Discussionmentioning
confidence: 99%
“…Noise from wind turbines appears to disturb animals, hinder their vocal communication, and their ability to hear predators leading to modified habitat use (Rabin, Coss, & Owings, 2006;Shannon et al, 2016). Furthermore, prey animals like reindeer react to movements in their sight (D'Angelo et al, 2008;Heesy, 2004) and may, therefore, react to the movement of the turbine blades. To our knowledge, there is only one study of wind turbine noise and visual cues on free-living terrestrial animal behavior, performed on ground squirrels (Rabin et al, 2006), and there seem to be no previous studies of possible impacts of sight and sound from WFs on either free-ranging reindeer or caribou.…”
Section: Introductionmentioning
confidence: 99%
“…However, the visual capabilities of white‐tailed deer are poorly described (VerCauteren and Pipas ). An understanding of deer vision can provide a foundation for understanding deer ecology as well as the development of more effective camouflage for hunters and wildlife viewers or strategies to reduce vehicular collisions with deer and other deer–human conflicts (Blackwell and Seamans , D'Angelo et al ).…”
mentioning
confidence: 99%
“…The white‐tailed deer eye is a typical mammalian eye; light enters through the cornea, and passes through the aqueous humor, pupil, lens, and vitreous humor before striking the retina (a layered neural structure in the back of the eye containing photoreceptors [Walls ]). White‐tailed deer eyes are well‐adapted to function at a wide range of ambient lighting conditions (D'Angelo et al ). For example, a horizontal slit pupil allows the deer eye to function properly in full daylight (Ali and Klyne ), while enhancing its visual acuity by directing light onto a strip of retinal cells containing a relatively high density of photoreceptors (Malmström and Kröger ).…”
mentioning
confidence: 99%
“…Various scientific studies have focused on strategies to minimize deer–vehicle collisions (DVCs) and to reduce damage to cultivated plants (VerCauteren et al 2003, 2006; Blackwell and Seamans 2008). However, despite some understanding about white‐tailed deer visual and auditory physiology (Jacobs et al 1994; D'Angelo et al 2007, 2008), little research has confirmed how deer perceive their environment through sight and sound (Zacks and Budde 1983, Zacks 1985, Birgersson et al 2001, VerCauteren and Pipas 2003, Heffner and Heffner 2010). Even then, interpretation of these studies is difficult due to small sample size and the cognition systems of animals (Jacobs 1993, VerCauteren and Pipas 2003).…”
mentioning
confidence: 99%